Comparative proteomics analysis of Shiraia bambusicola revealed a variety of regulatory systems on conidiospore formation - Du, Wen; Sun, Chunlong; Wu, Tao; Li, Wang; Dong, Bin; Wang, Baogui; Shang, Shuai; Yang, Qian; Huang, Wenwen; Chen, Shaopeng (Frontiers in Microbiology, 2024)
Shiraia bambusicola is a typical parasitic medicinal fungus of the family Shiraiaceae. The fruiting bodies of S. bambusicola cannot be cultivated artificially, and active substances can be effectively produced via fermentation. The mechanism of conidia production is a research hotspot in the industrial utilization and growth development of S. bambusicola. This study is the first to systematically study the proteomics of conidiospore formation from S. bambusicola. Near-spherical conidia were observed and identified by internal transcribed spacer (ITS) sequence detection.A total of 2840 proteins were identified and 1976 proteins were quantified in the mycelia and conidia of S. bambusicola. Compared with mycelia, 445 proteins were differentially expressed in the conidia of S. bambusicola, with 165 proteins being upregulated and 280 proteins being downregulated. The Gene Ontology (GO) annotation results of differential proteomics showed that the biological process of S.bambusicola sporulation is complex. The Kyoto Encyclopedia of Genes and Genomes (KEGG) metabolic pathway analysis showed that the differential proteins were mainly involved in starch and sucrose metabolism, biosynthesis of secondary metabolites, microbial metabolism in diverse environments, and other processes. Our in-depth speculative analysis showed that proteins related to carbohydrate metabolism were differentially expressed in conidiospore formation of S. bambusicola, suggesting the involvement of saccharides. Conidiation may increase the synthesis and release of ethanol and polysaccharide proteins such as glycoside hydrolase (GH), suppress host immunity, and facilitate S. bambusicola to infect and colonize of the host. In-depth analysis of differential proteomes will help reveal the molecular mechanism underlying the conidiospore formation of S. bambusicola, which has strong theoretical and practical significance.